Pengaruh variasi ukuran partikel terhadap nilai konduktivitas termal papan partikel tongkol jagung - Nanda Pratama (Department of Physics – Universitas Negeri Padang UNP, 2016)
Corncobs by most people still not optimally utilized, even considered as a waste byproduct of the primary production of maize. The content of lignocellulosic on corn cob allows for the manufacture of particle board by testing the thermal conductivity of which is expected later can be used as a heat insulator. The process of manufacture of particle board made with compression heat for 20 minutes with pressure of 160 Pa and temperature of 150 ° C, drying particle board for 15 days, density particle board 0.6x103 kg / m3 and thickness of particle board 1 cm.The results obtained for the thermal conductivity value of corncob particle board is greater mesh size, the smaller the size of its particles, the greater the thermal conductivity. From the results concluded that good particle board to serve as heat insulator materials are those that have low thermal conductivity values which qualify ukaran 8 mesh sieve amounted to 0.1012 W / m ° C. Increasingly smaller particle size makes thermal conductivity value increases so that the quality of heat insulator decreases